Research on Dynamic System of New Energy Food truck. Issue 2 (February 2019) - Yun Guo, Yufei Gao; Zhu, Yawen
Abstract: Mobile Food truck is very popular in Europe and America because of its convenient and quick advantages. But the study found that the majority of mobile Food trucks using traditional power and energy systems that is not very beneficial for environmental protection, In recent years, the field of mobile Food truck has the trend of light weight, convenience, multifunction and so on. How to make the use of Food truck cleaner, lower carbon and how to make it become a kind of green, environmental protection and healthy diet culture is very worthy of research and promotion of the subject for the office concentration of large and medium-sized cities.